One-punch man. 26, Unfathomable - ONE, 1986- (Shonen Jump manga., 2023)
As the fight against the Monster Association big shots heats up, Class-S heroes find themselves locked in a desperate struggle, but Tornado is closing in on Gyoro-Gyoro's main body! Meanwhile, Blackluster confronts Garo, while Saitama wanders the labyrinth where the Monster Association is hiding"--